The Possibility of Determining The Cost of Common Stock on The Basis of Options Theory - Mustafa Kareem Abid Al-Anbari; Shatha Abdul Hussein Jaber (Journal of Madenat Alelem University College, 2021)
The current research aims to test a model that can contribute to reducing the cost of common stocks and thus the cost of capital, which is the options pricing model for Black and Scholes (Bcs) (1973). The method of comparison used between the Capital Asset Pricing Model (CAPM) and options pricing for Black and Scholes (Bcs) was in calculating the cost of ordinary shares according to the weighted cost comparison of ordinary shares according to the two models, and the research sample included (8) industrial companies listed on the Iraq Stock Exchange that met the search conditions for the period (2008-2019).     The research reached a set of conclusions, the most important of which is that the weighted cost of ordinary shares according to the Bcs method is better than the weighted cost of ordinary shares according to the capital asset pricing method (CAPM), as the (Bcs) method recorded a good value in reducing costs. The research recommends adopting the options pricing model in the industrial sector companies, as it gave good results in reducing the cost of common.